Direct thiol-ene photocoating of polyorganosiloxane microparticles - Kuttner, Christian; Maier, Petra C.; Kunert, Carmen; Schlaad, Helmut; Fery, Andreas (Langmuir, 2013)
This work presents the modification of polyorganosiloxane microparticles by surface-initiated thiol-ene photochemistry. By this photocoating, we prepared different core/shell particles with a polymeric shell within narrow size distributions (PDI = 0.041-0.12). As core particle, we used highly monodisperse spherical polyorganosiloxane particles prepared from (3-mercaptopropyl) trimethoxysilane (MPTMS) with a radius of 0.49 μm. We utilize the high surface coverage of mercaptopropyl functions to generate surface-localized radicals upon irradiation with UVA-light without additional photoinitiator. The continuous generation of radicals was followed by a dye degradation experiment (UV/vis spectroscopy). Surface-localized radicals were used as copolymer anchoring sites ("grafting-onto" deposition of different PB-b-PS diblock copolymers) and polymerization initiators ("grafting-from" polymerization of PS). Photocoated particles were characterized for their morphology (SEM, TEM), size, and size distribution (DLS). For PS-coated particles, the polymer content (up to 24% in 24 h) was controlled by the polymerization time upon UVA exposure. The coating thickness was evaluated by thermogravimetric analysis (TGA) using a simple analytical core/shell model. Raman spectroscopy was applied to directly follow the time-dependent consumption of thiols by photoinitiation. © 2013 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20